The implementation of the merdeka curriculum: A study of educational management at secondary schools in Mataram, Indonesia - Muhammad Makki; Mohamad Mustari; Mansur Hakim; Muhammad Fachry (Kuras Institute, 2026)
Purpose − The Merdeka Curriculum provides greater flexibility for schools to design, implement, and evaluate learning programs according to their contextual needs. However, its successful implementation requires effective school management practices. This study aims to explore how school management functions are implemented in the process of adopting the Merdeka Curriculum in secondary schools in Mataram City, Indonesia. Method − The study employed a qualitative case study approach involving six secondary schools consisting of three senior high schools and three junior high schools. Data were collected through observations, semi-structured interviews with principals, teachers, and school staff, as well as document analysis. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Findings − The findings reveal that school management in implementing the Merdeka Curriculum is carried out through four key stages: planning, organizing, implementation, and monitoring. In the planning stage, schools conduct curriculum planning meetings, diagnostic assessments, and teacher training programs. The organizing stage involves the establishment of curriculum development teams and teacher performance assessment teams. During implementation, teachers apply teaching modules aligned with the Merdeka Curriculum while schools conduct workshops and professional development activities to strengthen teachers’ competencies. Monitoring and evaluation are conducted through summative assessments, the National Assessment (ANBK), and the use of educational report data. These findings highlight the crucial role of school leadership and collaborative management in ensuring the effective implementation of the Merdeka Curriculum. The study contributes to the understanding of school-level management practices that can support curriculum reform in the Indonesian education system.